2021
DOI: 10.1038/s41419-021-03706-8
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia inhibitory factor regulates Schwann cell proliferation and migration and affects peripheral nerve regeneration

Abstract: Leukemia inhibitory factor (LIF) is a pleiotropic cytokine that stimulates neuronal development and survival. Our previous study has demonstrated that LIF mRNA is dysregulated in the peripheral nerve segments after nerve injury. Here, we show that LIF protein is abundantly expressed in Schwann cells after rat sciatic nerve injury. Functionally, suppressed or elevated LIF increases or decreases the proliferation rate and migration ability of Schwann cells, respectively. Morphological observations demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The proliferation and migration of Schwann cells in rats after sciatic nerve injury enabled nerve regeneration and substantial functional recovery (Q. Chen, Liu, Zhang, Li, & Yi, 2021). Schwann cells are a dominant glial cell type in the neural system and can promote axonal regeneration (Gonzalez-Perez et al, 2018).…”
mentioning
confidence: 99%
“…The proliferation and migration of Schwann cells in rats after sciatic nerve injury enabled nerve regeneration and substantial functional recovery (Q. Chen, Liu, Zhang, Li, & Yi, 2021). Schwann cells are a dominant glial cell type in the neural system and can promote axonal regeneration (Gonzalez-Perez et al, 2018).…”
mentioning
confidence: 99%
“…It can be observed that the group with Yi Sheng as the core was large, and there was more cooperation within the group. Yi Sheng worked at Nantong University, China, where he focused on microRNA ( 38 , 39 ), and Schwann cells ( 40 , 41 ). Notably, most of the authors in this group were from East Asia, and there was less collaboration with authors from Europe.…”
Section: Resultsmentioning
confidence: 99%
“…LIF is a member of the IL-6 family of cytokines, expressed during inflammation. It has been reported to upregulate in response to different types of retinal diseases and possess various pharmacological effects, including promoting and inhibiting retinal vascular development, protecting the integrity of the vasculature, preventing retinal injury, and displaying neuroprotective properties 23–25. There were few studies on the levels of LIF in PCV and nAMD.…”
Section: Discussionmentioning
confidence: 99%